Trophy Hunting and Conservation in Africa: Problems and One Potential Solution - LINDSEY, PETER A; FRANK, L.G; ALEXANDER, R; MATHIESON, A; ROMAÑACH, S.S (Conservation biology, 2007)
Various problems and solution regarding trophy hunting and conservation in Africa are discussed. Lack of scientific data on the ecological and economic impact of trophy hunting precludes objective assessment of its role as a conservation tool in Africa. Discussion of trophy hunting in popular media is emotive and polarized, with animal welfare and animal rights groups on one side and hunters and pragmatic conservationists on the other. The small network of conservationists with specialized knowledge of the African trophy-hunting industry typically shares knowledge through verbal communication and gray literature. A brief overview of African trophy hunting and its role as a conservation tool are provided and a potential solution to problems associated with the industry is presented.